Sengketa Perbatasan Wilayah Kashmir Dalam Perspektif Hukum Internasional - Khaeruddin, Khaeruddin (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
Abstrak This study aims to discuss the Kashmir border dispute from the perspective of international law. The research method used in this study is qualitative. Qualitative research produces information in the form of notes and descriptive data found within the text being studied, utilizing data collection methods that are deemed relevant to the issues at hand and are characterized as a literature study. This research explains that Kashmir is a region coveted by two countries, India and Pakistan, leading to a highly disruptive conflict in South Asia. Based on the findings, the conflict between India and Pakistan over the Kashmir region is considered a dispute according to international law, as both India and Pakistan claim the territory. The Kashmir dispute arises from two main factors: religion and borders. Since the conflict between India and Pakistan over Kashmir is an international conflict, its resolution also involves international organizations such as SAARC and the United Nations.